c - G. S. S. (Chennai : Thamarai Brothers Media Private Limited, 2019)
Some of your wrong tendencies may also be due to wrong assumptions. But if you know what they are, then you can change yourself. The main reason for the breakdown of relationships is not recognizing the changes that occur in others. Those who recognize them and accept those changes will definitely succeed in their lives. This author has written very beautifully that when you change your perspective, a great change for success will occur in your life.
Text in Tamil.
Keywords: Self-actualization (Psychology); Self-actualization (Psychology)